PERENCANAAN SISTEM TRANSMISI PENGGERAK KAPAL POLBENG II - Afriantoni; Jupri; Siswandi (Politeknik Negeri Bengkalis, 2023)
The ship propulsion system generally consists of 3 (three) main components, namely: main engine, transmission system and propulsor. The ship's power propulsion transmission system in general starts from the main engine to the gearbox, shaft, stern tube for the shaft and shaft bearings, and propeller. The research aims to obtain the ship's main propulsion engine and propulsion transmission system components to be installed on the ship of Polbeng II that to be built. The planning of ship propulsion engine and its systems on ships needs to be done in order to obtain engine power and transmission systems that are in accordance with the propulsion needs of the ships being built. The planned ship is a passenger ship with the main size of the ship, Lpp = 9.8 m, B = 1.8 m, H = 1 m, T = 0.6 m and a speed of 21 knots. The results of the calculations are obtained, with a ship resistance of 5.7 kN, the main engine power is 98 HP. In the transmission system, the gearbox, shaft, bearings and propeller are installed from the main engine, with a gearbox ratio (1:3) and a propeller shaft size that is installed 1 3⁄4”. Keywords: propulsion system, engine power, transmission system, shaft